Political risk on Polish capital market - Dziawgo, Leszek (Ekonomia i Prawo. Economics and Law, 2020)
Motivation: The problem of political risk occurrence in the functioning of the economy should be subjected to scientific analysis. At the same time, various manifestations of political risk, its intensity and effects can be pointed out. Since the capital market is also an essential part of the modern economy, the following relationships should be analyzed: political risk — capital market. Aim: The purpose of the article is to draw attention to political risk on the Polish capital market and to present the results of own research on this issue. Results: The article describes selected aspects of political risk on the Polish capital market. The analysis includes both theoretical and empirical approach. An important part of the study is the presentation of the results of own research conducted on a sample of individual investors in 2014 and 2020 with the support of the Polish Association of Individual Investors. In the opinion of individual investors, the negative impact of political risk on the Polish capital market is increasing.